2018
DOI: 10.2478/sbe-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Factors Influencing Students' Intention to Adopt E-Learning in a Small Island Developing State (SIDS) Economy: Evidence from Mauritius

Abstract: This study is designed to investigate the factors influencing students' intention to adopt electronic learning (e-learning) in a Small Island Developing State (SIDS) economy. The overarching theory underpinning this study is the Technology Acceptance Model (TAM) which has been extended to include the learner's computer self-efficacy, the course flexibility and the instructor's attitude dimensions. Constructs from this extended TAM were used to design a questionnaire that was administered among 494 students usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…However, the findings of this study show that online teaching in Mauritius is more of a contingency plan to maintain continuity of teaching and learning during school closures rather than a well-planned system based on the mentioned imperatives, as highlighted by the participants. The outcomes of this study actually align with the findings of Sannegadu et al (2018) who showed that the adoption of innovative mode of e-learning is still limited in Mauritius due to the lack of learners' self-efficacy and teachers' attitudes and intentions of teachers to the use of online system.…”
Section: Effectivenesssupporting
confidence: 86%
See 1 more Smart Citation
“…However, the findings of this study show that online teaching in Mauritius is more of a contingency plan to maintain continuity of teaching and learning during school closures rather than a well-planned system based on the mentioned imperatives, as highlighted by the participants. The outcomes of this study actually align with the findings of Sannegadu et al (2018) who showed that the adoption of innovative mode of e-learning is still limited in Mauritius due to the lack of learners' self-efficacy and teachers' attitudes and intentions of teachers to the use of online system.…”
Section: Effectivenesssupporting
confidence: 86%
“…In most cases, examinations have either been cancelled. In fact, most grades from grade 1 to 13 have been cancelled, instead of shifting to contextualised 'Online Learning Assessment system'" "There is a real need to develop a contextualised online assessment mechanism in the education system" These findings are backed by several researchers such as Ramkissoon, Belle & Bhurosy (2020), Sannegadu, Seethiah, Dookhony, Gunesh & Jagessur (2018), Kattoua, Al-lozi & Alrowwad (2016), Tarhini, Hone & Liu (2014), Al-Adwan et al (2013, Shroff et al (2011) andCgaran &Pavri (2004) who showed that if not properly planned and stakeholders not properly trained, online teaching and learning cannot be effective. Qadir (2020) explained that effectiveness of online education depends on setting the proper mechanism that ensures that quality, inclusiveness and equity imperatives of online Covid-19 Impacts On Digital Education In Mauritius: A Digital Readiness Analysis teaching and learning are improved and at no point compromised.…”
Section: Effectivenessmentioning
confidence: 99%